COMMUNITY EFFORTS IN FLOOD AND LANDSLIDE - Fetri Elfada; Nazmi Nazmi; Iswandi Umar; Eri Barlian (Universitas Negeri Padang, 2020)
Research aims to analyze community efforts in overcoming natural disasters as well as floods and landslides. The research was conducted in Lima Puluh Kota District on the basis of the consideration that in that area there are frequent natural disasters of floods and landslides. The data was collected through open interviews, observation, and document review, then the data were analyzed descriptively qualitatively. The results showed. The mitigation efforts undertaken by the Gunung Malintang village government are as follows: 1) Design of the mitigation program in the Nagari RPJM 2016-2021, 2) Implementation of the gabion making program, 3) Conducting outreach, 4) Implementing the planting program on the river bank, 5) Conducting cooperation with the BPBD of Limapuluh Kota Regency. Apart from the Nagari government, mitigation efforts were also carried out by the BPBD of Limapuluh Kota Regency, namely as follows: 1) Destroying large rocks that obstruct the flow of water in the upstream area, 2) Placing an extension of the BPBD (SAR Team) arm. Efforts to overcome natural disasters require the participation and awareness of all parties (local government officials, social organizations, community leaders, community members, families) both in managing forests, maintaining smooth flow of rivers, drainage, maintaining conservation areas, and more urban spatial planning. good.